Assessing the New Model Fulfilling the Right to Education for Correctional Students - Darmawati Darma Kiki; Asriadi Zainuddin; Marwan Marwan; Arpin Arpin; Erni Dwita Silambi; Mardhati Mardhati (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2023)
The future of the Indonesian nation is very dependent on the condition of today's children. Therefore, future attention to children is the main focus, especially for Correctional Students (ADP) who live in the Special Child Development Institution (LPKA). One of the things that is of concern to children who are behind bars is the right to obtain formal and informal education. The purpose of this study was to analyze and evaluate the implementation of the fulfillment of the right to education for correctional students and to design an ideal model of fulfilling the right to education for children in Class II LPKA Gorontalo. The type of research used in this research is empirical normative legal research. The research results show that the educational process for ADP at LPKA is carried out in accordance with the mandate of Law Number 22 of 2022 concerning Corrections where ADP can pursue formal or informal education. In the implementation of formal learning process activities, there are still obstacles in the form of learning processes carried out outside LPKA, so it is necessary to formulate a learning model that should be made like a child-friendly school within LPKA and supported by educators who are truly competent and experienced in educating children.